Pharmacologic preconditioning of estrogen by activation of the myocardial adenosine triphosphate-sensitive potassium channel in patients undergoing coronary angioplasty - Lee, Tsung-Ming; Su, Sheng-Fang; Chou, Tsai-Fwu; Tsai, Chang-Her (Journal of the American College of Cardiology, 2002)
The purpose of this study was to determine whether administration of estrogen produces cardioprotective effects in patients undergoing coronary angioplasty. We have previously demonstrated that estrogen can provide cardioprotection by activating the mitochondrial adenosine triphosphate-sensitive potassium (KATP) channel, a major contributor to ischemic cardioprotection. Fifty patients undergoing angioplasty of a major epicardial coronary artery were randomly allocated to either ischemic preconditioning or intracoronary estrogen administration in the presence or absence of glibenclamide (glyburide). The coronary collateral circulation, as quantitatively assessed by an intracoronary Doppler flow wire, was similar during balloon inflation among the groups. Patients in the preconditioned and estrogen-treated groups significantly lowered their ischemic burden, as assessed by an ST-segment shift, chest pain score and myocardial lactate extraction ratio, as compared with control subjects. The reduction in the ST-segment shift afforded by estrogen during the first inflation (−63% vs. first inflation in the preconditioned group) was similar to that afforded by preconditioning during the second inflation (−68% vs. first inflation). In contrast, the patients given glibenclamide developed significantly higher ischemic burden during the first and second inflations, as compared with those in the estrogen-treated group alone. It is concluded that intracoronary administration of estrogen before balloon angioplasty rendered the myocardium relatively resistant to subsequent ischemia, and the degree of cardioprotective effect was comparable to that afforded by ischemic preconditioning. The effect of estrogen was abolished by glibenclamide, suggesting that the cardioprotective effect of estrogen may result from activation of myocardial KATPchannels.